Altitude asymmetry of ionospheric electron density depletion and recovery during the high latitude solar eclipse on June 10, 2021 - Sato, Hiroatsu; Nykiel, Grzegorz; Günzkofer, Florian Ludwig; Kodikara, Timothy; Hoque, Mohammed Mainul; Cahuasqui Llerena, Juan Andres (2024)
solar eclipse leads to a local decrease of ionospheric density that generally follow the obscuration function of the eclipse, whereas the recovery is often characteristically prolonged. Using EISCAT incoherent radar and GNSS measurements at high latitudes during the solar eclipse on June 10, 2021, we show that the electron density and temperature in the F-region respond asymmetrically in the top and bottom side of the ionosphere. The GNSS-derived total electron content (TEC) data show an eclipse-induced depletion of about 2 TECU, which persisted for at least a few hours in the post-eclipse period. The EISCAT data shows that the depletion and recovery profiles of the electron temperature in the F-region are consistent with the eclipse path across a wide range of altitudes. Conversely, the electron density at higher altitudes displayed delayed responses compared to lower altitudes. The EISCAT-derived TEC behaves similarly to the slow recovery of the GNSS TEC. Additionally, GRACE Follow-On satellite observations revealed a concurrent decrease in thermospheric neutral mass density during the eclipse. These findings suggest that the prolonged post-eclipse TEC recovery is influenced by dynamics in the ionosphere and thermosphere at higher altitudes.